2013
DOI: 10.1111/lcrp.12010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cross‐examination on children's reports of neutral and transgressive events

Abstract: Purpose. In many jurisdictions child witnesses who testify in court about their own sexual abuse are cross-examined by a defence attorney. Children find this process to be distressing, and despite recent child-focussed modifications to other aspects of the legal process, cross-examination has remained largely unaltered. This lack of modification is due, in part, to the assumption that cross-examination promotes truthful testimony (Wigmore, 1974 Evidence in trials at common law). However, little empirical resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…Suggestive questioning places pressure on children to reconsider and change their previous responses; both experimental (e.g., Zajac & Hayne, ; Fogliati & Bussey, ; Jack & Zajac, ) and field (Zajac et al, ; this study) research has shown that children are most likely to change their answers when questioned using closed‐ended suggestive prompts. In the present study, suggestive questions were more likely to elicit self‐contradictions than closed‐ended option‐posing prompts, open‐ended directives, and invitations, while option‐posing questions were more likely to elicit self‐contradictions than invitations.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Suggestive questioning places pressure on children to reconsider and change their previous responses; both experimental (e.g., Zajac & Hayne, ; Fogliati & Bussey, ; Jack & Zajac, ) and field (Zajac et al, ; this study) research has shown that children are most likely to change their answers when questioned using closed‐ended suggestive prompts. In the present study, suggestive questions were more likely to elicit self‐contradictions than closed‐ended option‐posing prompts, open‐ended directives, and invitations, while option‐posing questions were more likely to elicit self‐contradictions than invitations.…”
Section: Discussionmentioning
confidence: 75%
“…Children interviewed in the direct/direct condition were equally accurate in the two interviews, whereas children in the direct/cross condition were significantly less accurate when cross‐examined. Although some researchers have shown that these effects are stronger for younger than for older children (e.g., Zajac & Hayne, ; Bettenay, Ridley, Henry, & Crane, ), Fogliati and Bussey () reported no age differences in the number of errors elicited in cross‐examinations, perhaps because the age difference between the groups was so small.…”
Section: Children's Self‐contradictions In Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers instead encourage the use of open‐ended prompts such as free recall invitations (e.g., “Tell me what happened”) and directive prompts (e.g., “What did he do after your mum left?” when the child has previously disclosed that he did something after the mother left; see Lamb et al, ; Melton et al, for reviews; see Table ), which tend to elicit more accurate (Dent, , ; Jack, Leov, & Zajac, ; Lamb, Orbach, Hershkowitz, et al, ) and more detailed (e.g., Andrews & Lamb, ; Lamb, Orbach, Hershkowitz, et al, ; Sternberg, Lamb, Davies, & Westcott, ) responses. Furthermore, field studies have shown that few, if any, self‐contradictions are elicited using open‐ended invitations and directives (Andrews & Lamb, ; Fogliati & Bussey, ; Lamb & Fauchier, ). Despite these findings, lawyers predominantly use “risky” option‐posing and suggestive prompts when questioning children in court (e.g., Andrews & Lamb, ; Klemfuss, Quas, & Lyon, ).…”
Section: Research On Question Typesmentioning
confidence: 99%
“…Of interest, neither questioning style resulted in answers from the children that discriminated between liars and truth-tellers: Accuracy of the child liars increased in response to cross-examination, but accuracy of the child truth-tellers had a corresponding decrease. To the neutral questions, children's responses were consistent with their earlier responses regardless of whether or not those responses were truth or lies (see also Fogliati and Bussey 2014;Bussey 2015, Zajac et al 2017). Thus, overall, cross-examination was not helpful.…”
Section: Defendant Pro Se Cross-examination and Child Witness Accuracymentioning
confidence: 55%